THE SEMANTIC- PRAGMATIC MEANING OF THE SENTENCE - Tuhtaeva Shahzoda Oktamovna (TADQIQOTLAR, 2025)
Abstract: This work is based on the linguistic distinction, especially, from semantic and pragmatic directions, and the application of the semantic- pragmatic distinctions.